Effect of Gas Pressure and Electrode Distance on Self-Bias Voltage in Sputtering System for Thin Films - Ardiyanti, Aprilia Dewi (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The production of thin films using the sputtering preparation method is closely related to plasma. The deposition process involves several factors including self-bias voltage, sputter gas pressure, the distance between electrodes, and how to clean the substrate. This study will discuss the effect of variations in gas pressure and electrode distance on the resulting self-bias voltage. The method used is an RF sputtering system equipped with sensors for self-biased pressure and voltage readings. The results show that there is a corelations between pressure and electrode distance with self-biased voltage. Argon gas pressure variations are carried out in the range 4.5 – 8 x 10-2 mbar with variations for each increase in argon gas pressure of 0.5 x 10-2 mbar. The graph plot results show a logarithmic inversely proportional relationship, that is, when the pressure of argon gas is increased, there will be a decrease in self-bias voltage. The variation of the electrode spacing is carried out in the range 2 – 5 x 10-2 meters with a variation of each increase in the electrode distance of 1 x 10-2 meters. The corelations between the distance of electrodes and the self-biased voltage is logarithmic. When the electrode distance is increased there will be an increase in the value of the self-bias voltage.